Konvergensi Hukum Negara dan Syariat: Membaca Ulang Pengaturan Nafkah Anak Setelah Perceraian - H. Djuli, Sisinta (Judge : Jurnal Hukum, 2025)
This study aims to analyze the convergence of state law and sharia in the regulation of child support after divorce in Indonesia through a literature study with a qualitative normative approach. Data were collected from the analysis of primary legal documents such as Law No. 1/1974, KHI, and SEMA of the Supreme Court, as well as secondary sources in the form of journals and court decisions. The results of the study indicate that although there is harmonization between positive law and sharia in the principle of responsibility for support (Article 41 of the Marriage Law in conjunction with Article 80 of the KHI), the absence of a standard for the amount of support in the KHI causes disparities in court decisions. The implementation of the SEMA of the Supreme Court (No. 3/2015, No. 7/2012) as a dynamic reference also often does not take into account inflation and the real needs of children, while the absence of a monitoring mechanism for the execution of support decisions - especially for BUMN employees who are no longer subject to PP No. 10/1983 - is a serious challenge. The study concludes that the convergence of state law and sharia has not been fully effective in guaranteeing legal certainty for child support due to weak enforcement and the absence of a standard formula. For this reason, it is recommended: (1) codification of the KHI by including objective economic parameters, (2) strengthening the capacity of religious judges in assessing children's needs through special training, and (3) cross-sector collaboration between the courts, the Directorate General of Taxes, and social services for ongoing monitoring. These findings highlight the urgency of improving regulations that integrate the principles of economic justice with the protection of children's rights in a more comprehensive manner.